Service Quality Dimensions Influencing Online Buying Satisfaction Level of Customers in the Kathmandu Valley - Bohra, Raunak; Tamang, Puja (Journal of Business and Social Sciences Research, 2019)
This paper examines the factors influencing customer’s online shopping buying satisfaction level inside the Kathmandu Valley. It establishes a relationship between service quality dimensions with customer satisfaction in Nepalese online buying through correlation analysis. Seven service quality dimensions were selected for this research. They are information quality, usability, reliability, responsiveness, assurance, transaction security and personalisation. Data gathering was carried out developing a structured questionnaire which was distributed both through online and printed form using a convenience sampling method. The study has analysed the responses of 160 online shoppers (aged above 18 years) residing in the. The study confirms the absence of significant relationship between website usability and responsiveness while shows a positively significant relationship between other service quality (SERVQUAL) dimensions taken for this research. The proposed model in this study helps to ascertain the factors that influence online buying satisfaction level. Further, study concludes that while shopping online, websites with good layout and interaction helps promote customer satisfaction. Similarly, website reliability such as timely delivery of products, being truthful about its offerings, and fast delivery are considered as important elements for customer satisfaction.